2014
DOI: 10.1097/jto.0000000000000158
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chronic Obstructive Pulmonary Disease on the Mortality of Patients with Non–Small-Cell Lung Cancer

Abstract: COPD frequently and subliminally coexists with NSCLC. Although differences in clinical characteristic did exist, there was no impact of COPD on the mortality of patients with NSCLC with a positive smoking history in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 28 publications
9
63
0
1
Order By: Relevance
“…Although some argue that competing causes of death might dilute the mortality gains of screening smokers with COPD (34), the data do not bear this out (33). In all three studies that address this issue, after stratifying by the presence or absence of COPD on presurgery spirometry, comparable 5-year survival outcomes were found after surgical removal of early-stage NSCLC (35)(36)(37). If the differences in stage shift we found between COPD and no COPD were translated directly to mortality reduction, with no effect from competing causes of death or perioperative death from COPD, we estimate that the mortality reduction would be nearly twofold greater in those with COPD than in those with no COPD (66 and 34%, respectively).…”
Section: Discussionmentioning
confidence: 55%
“…Although some argue that competing causes of death might dilute the mortality gains of screening smokers with COPD (34), the data do not bear this out (33). In all three studies that address this issue, after stratifying by the presence or absence of COPD on presurgery spirometry, comparable 5-year survival outcomes were found after surgical removal of early-stage NSCLC (35)(36)(37). If the differences in stage shift we found between COPD and no COPD were translated directly to mortality reduction, with no effect from competing causes of death or perioperative death from COPD, we estimate that the mortality reduction would be nearly twofold greater in those with COPD than in those with no COPD (66 and 34%, respectively).…”
Section: Discussionmentioning
confidence: 55%
“…Most studies found that COPD exerted an unfavorable effect on lung cancer prognosis [78, 110, 111], while others did not [112, 113]. Two recent meta-analyses indicated COPD as an adverse prognostic predictor, but the results suffered from a high level of heterogeneity between studies [114, 115].…”
Section: Prognosis Of Lung Cancer With Copdmentioning
confidence: 99%
“…Improving our understandings of these associations has crucial public health implications, since the incidences of COPD and lung cancer have been steadily increasing worldwide. Some studies have suggested that lung cancer patients with COPD had poorer prognosis than those without, whilst other studies did not find differences in survival . Arca et al .…”
Section: Introductionmentioning
confidence: 98%